The use of enhanced half‐life coagulation factor concentrates in routine clinical practice: guidance from UKHCDO. (16th June 2016) - Collins, P.; Chalmers, E.; Chowdary, P.; Keeling, D.; Mathias, M.; O'Donnell, J.; Pasi, K. J.; Rangarajan, S.; Thomas, A.
Abstract : Enhanced half‐life factor VIII and IX products are being introduced into routine clinical practice. Published data report on clinical trials and there are limited data available on how to use these products in routine clinical practice. Many patients, for example, those with a past history of an inhibitor, have been excluded from clinical trials and there are limited data published on children. This guidance document is a consensus statement from the UK Haemophilia Centres Doctors' Organisation and aims to give pragmatic advice on the use of these products in routine practice.